Effect of Inorganic and Organic Zinc Supplementation on Feed Intake, Blood and Seminal Plasma Mineral Profile in Crossbred Bulls - Roy, B.; Nagpaul, P. K.; Pankaj, P. K.; Mohanty, T. K. (Indian Journal of Animal Nutrition, 2017)
Eighteen Karan Fries bulls were selected from Artificial Breeding Research Centre, ICAR-National Dairy Research Institute, Karnal, Haryana, India and randomly divided into 3 groups of 6 animals each in order to study the effect of inorganic or organic forms of Zn supplementation on feed intake and concentration of Zn,Cu and Ca in various biological samples (blood plasma, semen and hair). All the animals were fed as per NRC (2001) requirements. The animals in control group (T1) were not provided any supplemental Zn while those in groups T2 and T3 were supplemented with zinc sulfate and zinc propionate (27% available Zn) at 40 ppm level,respectively. The intakes of DM and CP were similar in all the groups. The Zn intake was higher (P